2017
DOI: 10.1017/s0031182017000294
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of toxoplasmosis in pregnancy. Evaluation of latex–protein complexes by immnunoagglutination

Abstract: The aim of this work was to obtain a reagent based on latex particles for ruling out acute toxoplasmosis in pregnant women by immunoagglutination (IA). Latex-protein complexes (LPC) were previously synthesized coupling the recombinant protein of Toxoplasma gondii P22Ag and the homogenate of the parasite to latex particles with different size, chemical functionality and charge density. LPC were tested in IA assays against a panel of 72 pregnant women serum samples. Results were analysed through receiver operati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Fifteen articles presented diagnosis performance on molecular diagnosis and/or bioassay and 23 articles analyzed serological performance diagnosis. Twenty-two articles in this review aimed at diagnosis improvement, 9 of them using a combination of diagnosis assays to improve performance [ 7 , 14 , 15 , 21 , 30 , 62 64 , 69 ] and 12 employing some modification of available methodologies [ 6 , 27 , 32 , 34 , 39 , 42 44 , 46 , 47 , 56 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…Fifteen articles presented diagnosis performance on molecular diagnosis and/or bioassay and 23 articles analyzed serological performance diagnosis. Twenty-two articles in this review aimed at diagnosis improvement, 9 of them using a combination of diagnosis assays to improve performance [ 7 , 14 , 15 , 21 , 30 , 62 64 , 69 ] and 12 employing some modification of available methodologies [ 6 , 27 , 32 , 34 , 39 , 42 44 , 46 , 47 , 56 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
“…The present results are in agreement with those conducted in Russia, and Prague showed that the seroprevalence was higher among subjects with blood group AB than among subjects with blood group O 25 , 27 previous studies reported in Baghdad province. 22 Previous studies suggested an association or relationship between the ABO blood group phenotypes and Toxoplasma , demonstrating that the parasite utilizes glycoconjugates that characterize the blood phenotypes of the ABO blood group system as potential receptors and the main route of infection. 18 , 19 Our present results disagree with the results that obtained by Faver et al, 12 in which there were no statistically significant differences between ABO blood group phenotypes and toxoplasmosis.…”
Section: Discussionmentioning
confidence: 99%
“…A homogenous appearance feature is interpreted as the absence of Toxoplasma gondii antibody (IgM/IgG), whereas clear serum agglutination is interpreted as the presence of Toxoplasma gondii antibody that may indicate or reflect either a past infection or evolving Toxoplasma gondii infection. [20][21][22]…”
Section: Latex Agglutination Testmentioning
confidence: 99%
See 1 more Smart Citation